Welcome to Westonci.ca, the place where your questions are answered by a community of knowledgeable contributors. Discover in-depth solutions to your questions from a wide range of experts on our user-friendly Q&A platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
[tex]y=2x-5 \\
4x-y=7 \\ \\
\hbox{substitute 2x-5 for y in the 2nd equation and solve for x:} \\
4x-(2x-5)=7 \\
4x-2x+5=7 \\
2x+5=7 \\
2x=7-5 \\
2x=2 \\
x=\frac{2}{2} \\
x=1 \\ \\
\hbox{substitute 1 for x in the 1st equation:} \\
y=2 \times 1-5=2-5=-3 \\ \\
\hbox{the answer:} \\
x=1 \\ y=-3[/tex]
This is straight forward:
You have already said: y = 2x - 5 ...........(i)
4x - y = 7............(ii)
So anywhere we see, y in equation (ii) we replace it with (2x - 5).
4x - (2x - 5) = 7
4x - 2x + 5 = 7
Note minus sign before the bracket, changes sign inside the bracket.
2x + 5 = 7
2x = 7 - 5.
2x = 2 Divide both sides by 2.
x = 2/2
x =1.
Remember from (i) y = 2x - 5, y = 2*1 - 5 = 2-5 = -3.
Therefore, x = 1, y = -3.
Those are the steps.
You have already said: y = 2x - 5 ...........(i)
4x - y = 7............(ii)
So anywhere we see, y in equation (ii) we replace it with (2x - 5).
4x - (2x - 5) = 7
4x - 2x + 5 = 7
Note minus sign before the bracket, changes sign inside the bracket.
2x + 5 = 7
2x = 7 - 5.
2x = 2 Divide both sides by 2.
x = 2/2
x =1.
Remember from (i) y = 2x - 5, y = 2*1 - 5 = 2-5 = -3.
Therefore, x = 1, y = -3.
Those are the steps.
We appreciate your time on our site. Don't hesitate to return whenever you have more questions or need further clarification. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.